Pendapatan, Pendidikan, Persepsi Kemudahan, dan Sikap sebagai Mediasi terhadap Keputusan Penggunaan Mobile Banking Syari’ah - Rosilia Salmah; Luqman Hakim (Jurnal Ilmiah Ekonomi Islam, 2021)
The existence of Covid-19 which limited society to transact online has made an increment several islamic banks in users and the number of transactions. The aim of this study was to review test how the influence of income, education, and perceived ease of use through attitude against the usage decision of shari’a mobile banking. A Structural Equation Model (SEM) was used to analyze in this study with WarpPLS 7.0 approach. Respondent of this research was general public of Surabaya City. Sampling technique which used in this study was purposive sampling as many as 115 respondents. The result present that perceived ease of use is the most significant factor affecting usage decision and attitude towards mobile banking directly. For the indirect test, perceived ease of use is able to influence the usage decision through attitude. Education and income not significantly influence the usage decision and attitude towards mobile banking directly, neither indirectly.